Biocatalysis as Key to Sustainable Industrial Chemistry. Issue 9 (3rd March 2022) - Alcántara, Andrés R.; Domínguez de María, Pablo; Littlechild, Jennifer A.; Schürmann, Martin; Sheldon, Roger A.; Wohlgemuth, Roland
Abstract: The role and power of biocatalysis in sustainable chemistry has been continuously brought forward step by step to its present outstanding position. The problem‐solving capabilities of biocatalysis have been realized by numerous substantial achievements in biology, chemistry and engineering. Advances and breakthroughs in the life sciences and interdisciplinary cooperation with chemistry have clearly accelerated the implementation of biocatalytic synthesis in modern chemistry. Resource‐efficient biocatalytic manufacturing processes have already provided numerous benefits to sustainable chemistry as well as customer‐centric value creation in the pharmaceutical, food, flavor, fragrance, vitamin, agrochemical, polymer, specialty, and fine chemical industries. Biocatalysis can make significant contributions not only to manufacturing processes, but also to the design of completely new value‐creation chains. Biocatalysis can now be considered as a key enabling technology to implement sustainable chemistry. Abstract : The golden age of biocatalysis : Biocatalysis can shorten chemical process routes and improve sustainability, as well as using cheaper and bio‐based raw materials, thereby reducing greenhouse gas emissions. Biocatalysis is well positioned to tackle synthetic challenges throughout process design and improve safety, health, economic and environmental aspects of large‐scale industrial production (difficulty levels: L=light; M=medium; D=difficult).